A Systematic and Generalizable Approach to the Heuristic Evaluation of User Interfaces. Issue 12 (2nd December 2018) - Alonso-Ríos, David; Mosqueira-Rey, Eduardo; Moret-Bonillo, Vicente
ABSTRACT: Heuristic evaluation is one of the most actively used techniques for analyzing usability, as it is quick and inexpensive. This technique is based on following a given set of heuristics, which are typically defined as broad rules of thumb. In this paper, we propose a systematic and generalizable approach to this type of evaluation based on using comprehensive taxonomies as a source for the heuristics. This approach contrasts with other typical approaches, such as following (or adapting) Jakob Nielsen's heuristics or creating ad hoc heuristics (formally or informally). The usefulness of our approach is investigated in two ways. Firstly, we carry out an actual heuristic evaluation of a mobile app in this manner, which we describe in detail. Secondly, we compare our approach and Nielsen's. Additionally, we identify some limitations in Nielsen's heuristics and some inconsistencies between them and established usability models, including Nielsen's own.